Improvement of organization of marketing service in textile enterprises - Musayeva Shoira Azimovna, (PT ANTIS International Publisher, 2024)
In this article, the integrated indicator of complex competitiveness, which includes resource competitiveness, investment, innovation, technological, marketing and logistics, management competitiveness, is discussed.